Ghosts of the deep – Biodiversity, fisheries, and extinction risk of ghost sharks. Issue 2 (2nd December 2020) - Finucci, Brittany; Cheok, Jessica; Ebert, David A.; Herman, Katelyn; Kyne, Peter M.; Dulvy, Nicholas K.
Abstract: Ghost sharks (subclass Holocephali) remain a largely data‐poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low proportion of threatened (8%) and Near Threatened (8%) species, with most species (69%) assessed as Least Concern. The group still exhibits some data deficiency (15%), and biological information is lacking for most species. Endemism is high, with 37% of species known from only one location or one country. Species richness was highest in the Northeast Atlantic, off the northwest coast of Africa (Morocco to Mauritania), the East China Sea, New Zealand and off the northwest coast of South America (Ecuador and Peru). Ghost sharks are predominately taken as by‐catch, but some targeted fishing and/or retention for the liver oil trade occurs. Species‐specific reporting, monitoring and management are required to assess population trends, and further investigation is needed on trade and use, particularly for higher risk species including the sicklefin chimaeras (genus Neoharriotta ) and the American Elephantfish ( Callorhynchus callorhynchus, Callorhinidae).